The ice dragon - Martin, George R. R.; Gilbert, Yvonne (New York : Tom Doherty Associates, 2006)
Leaving in its wake desolate cold and frozen land, the legendary ice dragon has never been tamed until it meets Adara, a winter child who looks to the creature to help save her world from destruction.
"A Starscape book"--T.p. verso.
"Originally published by Ace Books in the volume Dragons of light in 1980"--T.p. verso.
Keywords: Dragons -- Juvenile fiction; Fantasy fiction